Strategy deployment in business units : patterns of operations strategy cascading across global sites in a manufacturing firm - Schlickel, Maik. (Berlin, Heidelberg : Springer Berlin Heidelberg, 2015)
The author worked out that a company, which achieves to align its sound strategy cascading with the company context and leadership style of its top-management team, is likely to realize more operations improvements than do companies that missed to do so.
Includes bibliographical references (pages 183-187) and index.
oif 17/12/2019
Loans
Keywords: Strategic planning; Industrial management; Business planning; Economics